Lapidarne formy wideo jako nowy obszar oddolnych praktyk muzycznych - Juda, Łukasz (Narodowe Centrum Kultury, 2022)
This article analyses the musical layer of the currently extremely popular short videos, circulating in cyberspace, for example, on TikTok. As a new sphere of musical practices, these forms are attracting increasingly larger audiences, with active users recruiting particularly from among the youngest. As a result, prosumers have been given an unprecedented opportunity to create short, emergent, sound-based messages using primarily popular music. The article describes the growing ties between music and other media components due to media convergence, while also highlighting the role of music in the process of media divergence. The methods of mixing musical and extra-musical meanings as part of the bottom-up remix cul- ture are also analysed. The processes described in the text lead to the emergence of grassroots musical cyberpractices as part of a new multimedia form where the reformulated fragmented popular music – this highly intersubjective artifact of intermedia culture inseparably linked with image – plays a dominant role. As one of the most significant novelties in the recent development of cyberculture, this trend appears to be overcoming the visual centricity of the contemporary web, which has been repeatedly described in the literature of the subject.
Keywords: muzyka popularna; remiks; konwergencja; TikTok; lapidarne formy wideo; popular music; remix; convergence; TikTok; short videos